PS4:85 Fertility and pregnancy in women with systemic lupus erythematosus: a comparison with other rheumatic diseases. (21st March 2018) - Chalmeta-Verdejo, IC; Arevalo, K; Ivorra, J; Diaz-García, C; Negueroles, R; Grau, E; Gonzalez-Puig, L; Martinez-Cordellat, I; Feced, C; Ortiz, F; Alcañiz, C; Vicens, E; et al.
Abstract : Purpouse: Rheumatological disorders, usually affect women during reproductive ages and have an impact on their reproductive wishes. We aim to assess the differences between SLE and other diseases for fertility and pregnancy evolution in a group of patients followed in a specific consult for planning and management of pregnancy. Methods: Retrospective study in a cohort of patients with rheumatological disorders who want to get pregnant. Fertility exam to the couple was done. Data about sterility (never conception) and infertility (miscarriages), assisted reproduction, preterm delivery and also adverse pregnancy outcomes (disease flares, preeclampsia) were compared in 3 groups: SLE, connective tissue disease non-SLE (Sjögren's Syndrome, MCTD) and chronic arthritis (CA) including rheumatoid arthritis (RA), spondyloarthritis (SPA) and psoriatic arthritis (PsA). Results: 60 women (25 SLE, 9 connective tissue diseases non-SLE, 26 CA) were evaluated for pregnancy planning. All of them were in remission and were taking safe pharmacological treatment for the pregnancy. Fifty percent presented advanced maternal age (>35 years old) at the time of evaluation (8 SLE, 2 CTD no SLE and 15 CA). Until now, 48 patients have finished their pregnancy (18 SLE, 8 CTD non-SLE and 22 CA); in the others pregnancy is still on going. Data collected is showed in table. Sterility and fertility were similar in both, SLE and CA, and comparable with healthy women of the same age. Preeclampsia and an increased risk of preterm delivery were more frequent in the outcome of patients with SLE (p>0.05), however patients with CA showed basically joint inflammation (p>0.05). Antiphospholipid antibodies were not associated with higher rates of either fetal or maternal complications in this group of patient, probably because treatment with aspirin and LMWH was started at the beginning of conception. All neonates whose mothers were anti Ro positive (16 women) had positive anti Ro serum determination, however only four of them presented with atrioventricular block (AVB). Conclusion: In our group of patients, SLE showed comparable results of fertility with healthy women of the same age, probably because disease was in completed remission and they never use cyclophosphamide. Pregnancy planning help ensure better outcomes in these patients